Development of a hybrid model for website functional evaluation based on ISO/IEC 25010 and SERVQUAL - Prameswari, Ardiva Putri Tava; Setyawan, Muhammad Yusril Helmi (Matrix : Jurnal Manajemen Teknologi dan Informatika, 2025)
This study developed a hybrid model based on ISO/IEC 25010 and SERVQUAL to evaluate website quality holistically by combining technical dimensions and user perceptions. ISO / IEC 25010 is an international standard for evaluating the quality of software, including websites, based on technical characteristics such as Functional Suitability, Usability, Reliability, and Security. SERVQUAL, on the other hand, is used to measure quality based on user perception through five main dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. This study aims to identify the gaps between user expectations and the reality of website performance by using both frameworks. The research method combines quantitative and qualitative approaches, with user surveys and direct observation as data collection tools. The results of the analysis showed that most website quality dimensions, such as Functional Suitability, Usability, Reliability, Responsiveness, and Security, were in the category of "very adequate," with a relatively small gap between actual and expected scores. This study also tested the validity and reliability of constructs using convergent and discriminant analysis, as well as hypothesis testing to identify significant influences between variables. Hypothesis test results show that usability, reliability, and satisfaction variables have a significant influence on user experience. At the same time, factors such as functional fit and physical appearance do not directly affect user experience. This hybrid model provides theoretical contributions by enriching the literature on website Quality Evaluation and practical contributions by providing guidance for website managers to improve the quality of their services based on the identification of gaps between actual performance and user expectations.